Activation of a Modern Industry - Xie, Danyang (IMF Working Papers; Working Paper, 2002)
This paper constructs an integrated framework to disentangle the underlying economic mechanism of industrial transformation. We consider three essential elements for the analysis: skill requirements, industry-wide spillovers, and degrees of consumption subsistence. We find that human and nonhuman resources, production factor matching, and industrial coordination are all important for activating a modern industry. In the process of industrial transformation, job destruction may exceed job creation, and income distribution may get worse immediately following the activation of a modern industry. An array of policy prescriptions for advancing a poor country is provided.